EFFICIENCY COOPERATIVE AND ITS POTENTIAL FOR ABSORBING LABOR IN INDONESIA - Trisniarti, Noviami; Nur Sofyana, Nanda; Azhari, Azhari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The number of cooperatives in Indonesia reaches hundreds of thousands, but of the many cooperatives only 40% are active. The data also shows that employment in these business entities is less than 1% of the total workforce absorbed in various business sectors in Indonesia. The main objective of this study is to measure the efficiency of cooperatives in Indonesia and see the long-term relationship between cooperative productivity and employment in Indonesia. This research is quantitative by using two data analysis tools of envelopment analysis (DEA and cointegration test. Data envelopment analysis is to measure the efficiency of cooperatives. Meanwhile, to look at employment absorption using cointegration test. This research uses three inputs, namely, own capital, external capital, and the number of managers and one output is the profit of the cooperative.As for the cointegration test, the variable used is cooperative efficiency with the number of workers in the cooperative sector in Indonesia.The data used are primary and secondary data.Primary data are data obtained from the field and secondary data from the ministry of cooperatives and small and medium enterprises of the Republic of Indonesia.The results of this research show that the level of efficiency of cooperatives in Indonesia is not yet efficient, however there is a long-term relationship between cooperatives and employment in Indonesia.